PENGARUH DISIPLIN KERJA PEGAWAI NEGERI SIPIL TERHADAP KINERJA PEGAWAI PADA BAGIAN UMUM DAN KEPEGAWAIAN SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Yohanes . (ADMINISTRASI PUBLIK, 2018)
The purpose of this study is to determine whether employee discipline affect the performance of employees in the General and Personnel Division of the Regional Secretariat of East Kutai Regency. To get the data the authors do the research. The results showed that the discipline of employees is very important role in the performance of employees in the sense that the performance factor in the General and Officers Division of the Regional Secretariat of East Kutai Regency from month to month experienced an increased change in this followed by the discipline of employees who work as a cause, this is proven by the result of hepotesis test which shows that there is influence of work discipline of employee to employee performance.             To improve the performance of employees in addition to work discipline factors then other factors also need to get attention so that the performance of employees In the General Section and staffing Regional Secretariat..East..Kutai..District..can..be..improved.